2020
DOI: 10.3390/plants9081002
|View full text |Cite
|
Sign up to set email alerts
|

Trifolium repens-Associated Bacteria as a Potential Tool to Facilitate Phytostabilization of Zinc and Lead Polluted Waste Heaps

Abstract: Heavy metals in soil, as selective agents, can change the structure of plant-associated bacterial communities and their metabolic properties, leading to the selection of the most-adapted strains, which might be useful in phytoremediation. Trifolium repens, a heavy metal excluder, naturally occurs on metal mine waste heaps in southern Poland characterized by high total metal concentrations. The purpose of the present study was to assess the effects of toxic metals on the diversity and metabolic properties of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 86 publications
1
16
0
Order By: Relevance
“…The tolerance of C. juncea to PTE might be linked to its root symbiosis with nitrogen-fixing bacteria as previously reported for other leguminous 56 , 57 . Our data sustain this idea by the higher number of nodules in root parts of plants located in the contaminated area.…”
Section: Discussionsupporting
confidence: 64%
“…The tolerance of C. juncea to PTE might be linked to its root symbiosis with nitrogen-fixing bacteria as previously reported for other leguminous 56 , 57 . Our data sustain this idea by the higher number of nodules in root parts of plants located in the contaminated area.…”
Section: Discussionsupporting
confidence: 64%
“…There is no doubt that cultivation of T. fragiferum in heavily metal-contaminated soils will leed to accumulation of these heavy metals in above ground parts well above permissable levels. However, both heavy metal tolerance and accumulation potential in natural conditions can be significantly affected by symbiosis with arbuscular mycorrhiza and associated rhizobacteria, as in the case of T. repens (Oleńska et al 2020;Xiao et al 2020;Xiao et al 2021) and T. pratense (Vivas et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, plant species belonging to the Leguminosae family, such as Medicago lupulina, Lotus corniculatus, and Trifolium repens, were reported to make major contribution to phytostabilization (Amer et al, 2013;Bert et al, 2000;Bidar et al, 2007), whereas only Medicago lupulina showed some Pb translocation ability to aerial parts (Amer et al, 2013). The tolerance of Trifolium repens to contaminated sites should also be noted, with the roots being the main organ of Pb accumulation (Bidar et al, 2007;Oleńska et al, 2020). In another study, Lotus corniculatus showed the bioaccumulation of PTEs not exceeding current legal limits for Cd, Cr, and Pb.…”
Section: Ptes In the Plant/soil Systemmentioning
confidence: 99%